Monetary integration in east Asia: A hierarchical clustering approach - Quah, Chee-Heong.; Crowley, P.M. (Blackwell Publishing, 2010)
Currently, a number of the fastest growing economies in the world are located in East Asia. Given these countries' dominance in the region, any monetary integration scheme in Asia would likely have to include them. This paper attempts to assess the evolution of convergence among the East Asian countries according to optimum currency area theory operationalized using a hierarchical cluster analysis. The clustering exercise is done for periods before and after the Asian crisis of 1997-98. The results suggest a significant rise in the degree of regional symmetry after the Asian crisis.